2016
DOI: 10.3390/nu8010060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cudrania tricuspidata and Kaempferol in Endoplasmic Reticulum Stress-Induced Inflammation and Hepatic Insulin Resistance in HepG2 Cells

Abstract: In this study, we quantitated kaempferol in water extract from Cudrania tricuspidata leaves (CTL) and investigated its effects on endoplasmic reticulum (ER) stress-induced inflammation and insulin resistance in HepG2 cells. The concentration of kaempferol in the CTL was 5.07 ± 0.08 mg/g. The HepG2 cells were treated with 300 µg/mL of CTL, 500 µg/mL of CTL, 1.5 µg/mL of kaempferol or 2.5 µg/mL of kaempferol, followed immediately by stimulation with 100 nM of thapsigargin for ER stress induction for 24 h. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
0
16
0
2
Order By: Relevance
“…As a result, the enhanced expression of CHOP increases the level of apoptosis, leading to the decreased viability and proliferation of tumor cells (Guo et al, ). A study conducted by Kim, Jun, and Lee () provided a novel pathway of kaempferol action. In order to induce ER stress in HepG2 cells, thapsigarin was applied and findings demonstrated that this agent affects a number of signaling pathway to induce ER stress and subsequently, enhance insulin resistance by insulin receptor substrate‐1 (IRS‐1) induction.…”
Section: Kaempferol and Er Stressmentioning
confidence: 99%
“…As a result, the enhanced expression of CHOP increases the level of apoptosis, leading to the decreased viability and proliferation of tumor cells (Guo et al, ). A study conducted by Kim, Jun, and Lee () provided a novel pathway of kaempferol action. In order to induce ER stress in HepG2 cells, thapsigarin was applied and findings demonstrated that this agent affects a number of signaling pathway to induce ER stress and subsequently, enhance insulin resistance by insulin receptor substrate‐1 (IRS‐1) induction.…”
Section: Kaempferol and Er Stressmentioning
confidence: 99%
“…102 Kemiricilerde ER stresinin obezite ve metabolik disfonksiyonla ilişkisi olduğu bilinmesine rağmen, kilo kaybı sonucunda ER stres parametrelerinin nasıl değiştiğini inceleyen az sayıda çalışma bulunmaktadır. Özellikle, insanlarda obezite ve ER stresi arasındaki ilişkiyi inceleyen çalışmaların çok az sayıda olduğu görülmektedir.…”
Section: İnsan çAlişmalariunclassified
“…Bu sonuçlar, kaempferolun CTL içindeki aktif bileşen olduğunu ve ER stresiyle indüklenen inflamasyon ve hiperglisemiye karşı koruyucu olabileceğini göstermektedir. 102 Dehidroaskorbik asit (DHAA) vitamin C'nin okside türevidir ve diyabette bu türevin biyolojik sıvılardaki miktarının arttığı bilinmektedir. İnsan nöroblastoma hücreleri kullanılarak yapılan bir ça-lışmada, DHAA'nın ER stresi ve leptin rezistansı üzerine etkileri incelenmiştir.…”
unclassified
“…This issue provides an opportunity to update current knowledge about some examples of the six subclasses of the flavonoid compounds and their effects—even at molecular level—on immunity and inflammation, but also in inflammatory-mediated diseases such as insulin-resistance obesity, cardiovascular disease and even in cancer. The Special Issue contains six review papers [13,14,15,16,17,18] and eight research papers [19,20,21,22,23,24,25,26] on the current knowledge in the field. Contributions are from countries in Africa (South Africa), America (Brazil), Asia (China, Korea, Japan and Taiwan) and Europe (Germany, Spain and Switzerland).…”
mentioning
confidence: 99%
“…The Special Issue contains only one in vitro study showing that one flavonol—kaempherol—is able to partially inhibit stress-induced inflammation and hepatic insulin resistance in HepG2 cells [23]. On the other hand, although it is well established that the principal pharmacological action of phlorizin, a chalcone, is to produce renal glycosuria and to block intestinal glucose absorption through inhibition of the renal and mucosal sodium–glucose symporters, one article included in this issue highlights other complementary effects using an in vivo approach in obese mice, such as its action on hepatic steatosis, inflammation and fibrosis [26].…”
mentioning
confidence: 99%